1998
DOI: 10.1046/j.1365-2044.1998.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrathecal administration of magnesium sulphate in rats

Abstract: SummarySomatosensory evoked potential, locomotion and vocalisation upon tail pinch in rats was studied in order to determine whether intrathecal magnesium sulphate administration causes spinal anaesthesia. In Wistar rats with indwelling intrathecal catheters, cortical somatosensory evoked potential was recorded following stimulation via electrodes inserted into the hind paw under chloral hydrate anaesthesia before and after intrathecal administration of 10 ml of either magnesium sulphate (12.3% or 24.6%) or li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(32 reference statements)
1
9
1
1
Order By: Relevance
“…Our study is also in accordance with preclinical studies, which report that intrathecal magnesium suppresses neuropathic pain responses in different rat models, [20][21][22] and delays the development of tolerance when co-FIGURE 2 Effects of ip magnesium pretreatment vs ip saline pretreatment on the short-lasting effect (A) and on the long-lasting effect (B) induced by sc fentanyl 60 µg·kg -1 × 4 as measured by the paw-pressure vocalization test (n = 8 for each group). Mean nociceptive thresholds (± SD) are expressed in grams.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is also in accordance with preclinical studies, which report that intrathecal magnesium suppresses neuropathic pain responses in different rat models, [20][21][22] and delays the development of tolerance when co-FIGURE 2 Effects of ip magnesium pretreatment vs ip saline pretreatment on the short-lasting effect (A) and on the long-lasting effect (B) induced by sc fentanyl 60 µg·kg -1 × 4 as measured by the paw-pressure vocalization test (n = 8 for each group). Mean nociceptive thresholds (± SD) are expressed in grams.…”
Section: Discussionsupporting
confidence: 92%
“…Magnesium sulphate was dissolved in 0.9% saline, with the final dose always administered in a volume of 10 ml. Rats were divided into five groups and examined for the presence of locomotor dysfunction by an experimenter unaware of the drug concentration used [4,10]. Observations at 10-min intervals after intrathecal injection included the following: 1 Placing reflex.…”
Section: Locomotion Testmentioning
confidence: 99%
“…Intrathecal administration of magnesium sulphate (MgSO 4 ) has recently been shown to produce spinal anaesthesia [1][2][3]. Using the tail-pinch method, we have reported that intrathecal administration of MgSO 4 did not induce complete analgesia in the presence of motor paralysis [4] although differentiation of analgesia from motor paralysis may be difficult.…”
mentioning
confidence: 99%
See 2 more Smart Citations